Levosimendan prevents doxorubicin-induced cardiotoxicity in time- and dose-dependent manner: implications for inotropy - Efentakis, P; Varela, A.; Chavdoula, E; Sigala, F; Sanoudou, D.; Tenta, R; Gioti, K; Kostomitsopoulos, N.; Papapetropoulos, A.; Tasouli, A; Farmakis, D.; Davos, C.H.; et al. (Cardiovasc ResCardiovasc ResCardiovasc Res, 2020)
AIMS: Levosimendan (LEVO) a clinically-used inodilator, exerts multifaceted cardioprotective effects. Case-studies indicate protection against doxorubicin (DXR)-induced cardiotoxicity, but this effect remains obscure. We investigated the effect and mechanism of different regimens of levosimendan on sub-chronic and chronic doxorubicin cardiotoxicity. METHODS AND RESULTS: Based on preliminary in vivo experiments, rats serving as a sub-chronic model of doxorubicin-cardiotoxicity and were divided into: Control (N/S-0.9%), DXR (18 mg/kg-cumulative), DXR+LEVO (LEVO, 24 mug/kg-cumulative), and DXR+LEVO (acute) (LEVO, 24 mug/kg-bolus) for 14 days. Protein kinase-B (Akt), endothelial nitric oxide synthase (eNOS), and protein kinase-A and G (PKA/PKG) pathways emerged as contributors to the cardioprotection, converging onto phospholamban (PLN). To verify the contribution of PLN, phospholamban knockout (PLN-/-) mice were assigned to PLN-/-/Control (N/S-0.9%), PLN-/-/DXR (18 mg/kg), and PLN-/-/DXR+LEVO (ac) for 14 days. Furthermore, female breast cancer-bearing (BC) mice were divided into: Control (normal saline 0.9%, N/S 0.9%), DXR (18 mg/kg), LEVO, and DXR+LEVO (LEVO, 24 mug/kg-bolus) for 28 days. Echocardiography was performed in all protocols. To elucidate levosimendan's cardioprotective mechanism, primary cardiomyocytes were treated with doxorubicin or/and levosimendan and with N omega-nitro-L-arginine methyl ester (L-NAME), DT-2, and H-89 (eNOS, PKG, and PKA inhibitors, respectively); cardiomyocyte-toxicity was assessed. Single bolus administration of levosimendan abrogated DXR-induced cardiotoxicity and activated Akt/eNOS and cAMP-PKA/cGMP-PKG/PLN pathways but failed to exert cardioprotection in PLN-/- mice. Levosimendan's cardioprotection was also evident in the BC model. Finally, in vitro PKA inhibition abrogated levosimendan-mediated cardioprotection, indicating that its cardioprotection is cAMP-PKA dependent, while levosimendan preponderated over milrinone and dobutamine, by ameliorating calcium overload. CONCLUSION: Single dose levosimendan prevented doxorubicin cardiotoxicity through a cAMP-PKA-PLN pathway, highlighting the role of inotropy in doxorubicin cardiotoxicity.
Efentakis, PanagiotisVarela, AimiliaChavdoula, EvangeliaSigala, FragiskaSanoudou, DespinaTenta, RoxaneGioti, KaterinaKostomitsopoulos, NikolaosPapapetropoulos, AndreasTasouli, AndronikiFarmakis, DimitriosDavos, Costantinos HKlinakis, ApostolosSuter, ThomasCokkinos, Dennis VIliodromitis, Efstathios KWenzel, PhilipAndreadou, IoannaengResearch Support, Non-U.S. Gov'tEngland2019/06/23 06:00Cardiovasc Res. 2020 Mar 1;116(3):576-591. doi: 10.1093/cvr/cvz163.
Keywords: Animals; Antibiotics, Antineoplastic/*toxicity; Calcium Signaling; Calcium-Binding Proteins/genetics/metabolism; Cardiotoxicity; Cardiovascular Agents/*pharmacology; Cells, Cultured; control; Cyclic AMP-Dependent Protein Kinases/metabolism; Cyclic AMP/metabolism; Cyclic GMP-Dependent Protein Kinases/metabolism; Cyclic GMP/metabolism; Dose-Response Relationship, Drug; Doxorubicin/*toxicity; Female; Heart Diseases/chemically induced/metabolism/physiopathology/*prevention &; Male; Mammary Neoplasms, Experimental/*drug therapy/metabolism/pathology; Mice, 129 Strain; Mice, Inbred C57BL; Mice, Knockout; Myocardial Contraction/*drug effects; Myocytes, Cardiac/*drug effects/metabolism/pathology; Nitric Oxide Synthase Type III/metabolism; Proto-Oncogene Proteins c-akt/metabolism; Rats, Wistar; Simendan/*pharmacology; Time Factors